A revision of the spider genus Raveniola (Araneae, Nemesiidae). I. Species from Western Asia - Zonstein, Sergei; Kunt, Kadir B.; Yağmur, Ersen A. (European Journal of Taxonomy, 2018)
The genus Raveniola Zonstein, 1987 is found to be represented in Western Asia by 16 species: ♂♀ R. adjarica sp. nov. (Georgia), ♂ R. anadolu sp. nov. (Turkey), ♂ R. arthuri Kunt & Yağmur, 2010 (Turkey), ♂ R. birecikensis sp. nov. (Turkey), ♂♀ R. dunini sp. nov. (Armenia, Azerbaijan, Iran), ♂♀ R. hyrcanica Dunin, 1988 (Azerbaijan), ♂ R. marusiki sp. nov. (Iran), ♂ R. mazandaranica Marusik, Zamani & Mirshamsi, 2014 (Iran), ♂♀ R. micropa (Ausserer, 1871) (Turkey), ♀ R. nana sp. nov. (Turkey), ♂♀ R. niedermeyeri (Brignoli, 1972) (Iran), ♂♀ R. pontica (Spassky, 1937) (Russia, Georgia), ♀ R. sinani sp. nov. (Turkey), ♂♀ R. turcica sp. nov. (Turkey), ♂♀ R. vonwicki Zonstein, 2000 (Iran) and ♂♀ R. zaitzevi (Charitonov, 1948) (Azerbaijan, Georgia) = ♀ Brachythele recki Mcheidze, 1983, syn. nov. Eight species are newly described; others are redescribed from types and/or conspecific material. Males of R. micropa and R. zaitzevi, hitherto unknown, are described for the first time. Data on the variability, relationships, distribution, and ecology of all considered species are also provided.